2015
DOI: 10.2105/ajph.2014.302060
|View full text |Cite
|
Sign up to set email alerts
|

The Montana Radon Study: Social Marketing via Digital Signage Technology for Reaching Families in the Waiting Room

Abstract: Objectives I tested a social marketing intervention delivered in health department waiting rooms via digital signage technology for increasing radon program participation among priority groups. Methods I conducted a tri-county, community-based study over a 3-year period (2010–2013) in a high-radon state by using a quasi-experimental design. We collected survey data for eligible participants at the time of radon test kit purchase. Results Radon program participation increased at the intervention site (t38 =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 21 publications
0
15
0
Order By: Relevance
“…( Table 1 , column 2: ‘Practice speciality’) was diverse primary healthcare services, only two studies being explicitly run in general practice [ 16 , 23 ]. In several cases, the typology of primary healthcare was not mentioned (‘routine PHC’) [ 15 , 22 , 25 ], or seemed orientated towards preventive care [ 17 , 21 ]. In six cases, settings were orientated towards mother and child services [ 13 , 14 , 18 ], family planning, and sexually transmitted diseases [ 19 , 20 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…( Table 1 , column 2: ‘Practice speciality’) was diverse primary healthcare services, only two studies being explicitly run in general practice [ 16 , 23 ]. In several cases, the typology of primary healthcare was not mentioned (‘routine PHC’) [ 15 , 22 , 25 ], or seemed orientated towards preventive care [ 17 , 21 ]. In six cases, settings were orientated towards mother and child services [ 13 , 14 , 18 ], family planning, and sexually transmitted diseases [ 19 , 20 , 24 ].…”
Section: Resultsmentioning
confidence: 99%
“…Future research should assess patterns of radon testing, barriers to radon mitigation, and develop interventions and public health programs to improve awareness about radon and access to radon mitigation procedures. Previous interventions that provided tailored information and guidance to households and in primary care settings are effective at increasing awareness [ 38 40 ]. Differences in access to lung cancer screening and delays in treatment by geographic area, and the cumulative impact of smoking, radon exposure, and socioeconomic risk factors on lung cancer incidence and survival among nonmetropolitan residents in should be explored in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…The app is a very different style of content delivery than the explanations typically used in pamphlets and brochures [11,12] or in telephone interviews [9,10]. With several notable exceptions [8,12,23]e.g., an increase in radon test kit purchases reported among individuals exposed to digital signs in physicians' waiting rooms [8] few intervention studies have reported that the intervention improved individuals' knowledge, attitudes, perceptions, or behaviors.…”
Section: Summary Of Findings and Limitationsmentioning
confidence: 99%
“…Several studies have developed educational interventions concerning radon and a few have tested their effectiveness [8][9][10][11][12]. To the extent that interventions have been tested, most have performed poorly when measured against "real world" outcomes, such as increases in testing rates and home remediation.…”
Section: Introductionmentioning
confidence: 99%